The correlation between cognitive styles and written corrective feedback preferences among Iranian and Turkish EFL learners - Kivi, Parivash Jamali (2021)
This study aimed at finding the correlation between Iranian and Turkish EFL learners’ cognitive styles and their preferences for different WCF types. Sixty out of seventy-five EFL students at the intermediate level in two contexts (Iran and Turkey) were selected through the Oxford Placement Test. There were two instruments in this research: The Learning Styles Questionnaire, and CF questionnaire. The researcher gave detailed instructions on how to complete the surveys. The findings demonstrated that there was a correlation between EFL students’ cognitive styles and their WCF preferences in both Iran and Turkey contexts. The second research question results indicated that there was a relationship between learners’ cognitive styles and their preferences for different types of errors to be corrected. The results of the third research question showed that the correlation between Iranian students’ cognitive styles and their preferences for different CF frequencies was not significant. The last research question results showed that the correlation between Turkish students’ cognitive styles and their preferences for different CF frequencies was not significant.